2012
DOI: 10.1111/gtc.12015
|View full text |Cite
|
Sign up to set email alerts
|

ROS‐generating oxidases Nox1 and Nox4 contribute to oncogenic Ras‐induced premature senescence

Abstract: Activated oncogenes induce premature cellular senescence, a permanent state of proliferative arrest in primary rodent and human fibroblasts. Recent studies suggest that generation of reactive oxygen species (ROS) is involved in oncogenic Ras-induced premature senescence. However, the signaling mechanism controlling this oxidant-mediated irreversible growth arrest is not fully understood. Here, we show that through the Ras/MEK pathway, Ras oncogene upregulated the expression of superoxide-generating oxidases, N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
67
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(71 citation statements)
references
References 33 publications
4
67
0
Order By: Relevance
“…ROS generation is mediated through activation of NADPH oxidase 45. In our study, NOX4 expression increased in cytokine‐treated IHOK, whereas NOX1 expression was reduced.…”
Section: Discussionsupporting
confidence: 49%
“…ROS generation is mediated through activation of NADPH oxidase 45. In our study, NOX4 expression increased in cytokine‐treated IHOK, whereas NOX1 expression was reduced.…”
Section: Discussionsupporting
confidence: 49%
“…The pathological role of Nox4 is unclear, although it has been implicated in hypertension, atherosclerosis, and cardiovascular and renal complications of diabetes and in remodeling of pulmonary arteries in pulmonary hypertension (181,206). Nox4-derivd ROS has also been suggested in cellular senescence and aging (104) and in insulin-mediated differentiation of adipocytes (177). Recent studies demonstrated that Nox4 may actually have protective effects, possibly through Nox4-derived H 2 O 2 , which may act as a vasodilator in some vascular beds (164,238).…”
Section: Nox4mentioning
confidence: 99%
“…Several findings make it a good candidate. First, NOX4 is constitutively expressed and active in a large range of cells (9); second, it is localized to the immediate environment surrounding the nucleus so that ROS generated there could be responsible for the increased levels of oxidative DNA damage found in A-T cells (11)(12)(13); third, NOX4 has been found to be involved in senescence, a major phenotype exhibited by primary A-T cells (12,20,21).…”
mentioning
confidence: 99%